Studi Kitab Hadis: Kitab Al-Nihayah Fi Al-Fitan Wa Al-Malahim Karya Ibnu Katsir - risqo faridatul ulya; Ummi Kalsum Hasibuan (Jurnal Ulunnuha, 2020)
This article examines the study of the hadith book, namely the book al-Nihayah fi al-Fitan wa al-Malahim by Ibn Kathir which refers to the biography of Ibn Kathir and the general description of the book, its characteristics, methods and systematics of discussion, as well as the advantages and disadvantages of the book. This article aims to examine the book al-Nihayah fi al-Fitan wa al-Malahim in a comprehensive manner, and to provide lessons for readers to know the events of the last day. The method used in this writing is descriptive-qualitative method. The result of the research is that this book is compiled to complement the previous book entitled Al-Bidayah wa Al-Nihayah. The main discussion is about various kinds of slander or disasters, wars and major events towards the end of time and a picture of life in the hereafter. The systematics of this book begins with the theme of the Prophet's messages, regarding the signs of the end for Muslims, starting with the signs of a fire in the Hijaz region until the fall of Prophet Isa As. The method used is a thematic method, and the theme raised is eschatological hadith. Referring to sources such as the Koran, hadiths, and other narrations accompanied by explanations of the truth of the hadith. This book consists of one volume with two discussion chapters. The discussion in this book also describes several traditions (having different eyes but has the same meaning) and describes a hadith that ends with an explanation of the traditions of the hadith in the book.